The changes in relation of auditory and visual input activity between hemispheres analized in cartographic EEG in a child with hyperactivity syndrome - Radičević, Zoran; Jeličić, Ljiljana; Bogavac, Ivana; Stokić, Miodrag; Sovilj, Mirjana; Subotić, Miško (Specijalna edukacija i rehabilitacija, 2015)
The paper discusses the changes in relations of visual and auditory inputs between the hemispheres in a child with hyperactive syndrome and its effects which may lead to better attention engagement in auditory and visual information analysis. The method included the use of cartographic EEG and clinical procedure in a 10-year-old boy with hyperactive syndrome and attention deficit disorder, who has theta dysfunction manifested in standard EEG. Cartographic EEG patterns was performed on Nihod Kohden Corporation, EEG – 1200K Neurofax apparatus in longitudinal bipolar electrode assembly schedule by utilizing 10/20 International electrode positioning. Impedance was maintained below 5 kΩ, with not more than 1 kΩ differences between the electrodes. Lower filter was set at 0.53 Hz and higher filter at 35 Hz. Recording was performed in a quiet period and during stimulation procedures that include speech and language basis. Standard EEG and Neurofeedback (NFB) treatment indicated higher theta load, alpha 2 and beta 1 activity measured in the cartographic EEG which was done after the relative failure of NFB treatment. After this, the NFB treatment was applied which lasted six months, in a way that when the boy was reading the visual input was enhanced to the left hemisphere and auditory input was reduced to the right hemisphere. Repeated EEG mapping analysis showed that there was a significant improvement, both in EEG findings as well as in attention, behavioural and learning disorders. The paper discusses some aspects of learning, attention and behaviour in relation to changes in the standard EEG, especially in cartographic EEG and NFB findings.